Factors Related to Musculoskeletal Disorders (MSDs) on Traditional Fabric Weavers in Loce Village - Hermiana Sunarti Isi; Soni Doke; Sarci Magdalena Toy (Universitas Nusa Cendana, 2022)
Musculoskeletal Disorders (MSDs) are complaints of individuals in the skeletal muscles due to a non-ergonomic work attitude. Weave feeling is a type of work that operates in the informal sector and has a high risk of MSDs. This study aimed to determine the relationship between age factors, length of work, work period, work posture, and MSDs in traditional cloth weavers in Loce Village, Manggarai Regency. This type of research was quantitative with an analytical survey method using a cross-sectional research design. This research was in Loce Village, Manggarai Regency, and carried out for two months, from November to December 2020. The sample in this study was 39 traditional cloth weavers in Loce Village, Manggarai Regency, taken by totaling sampling technique. The statistical test used was the chi-square test with a degree of confidence p = 0.05. The results showed that most of the respondents (76.9%) suffered MSDs, mostly located in the body of the left shoulder, right shoulder, and back. Statistical analysis results showed there was a relationship between the age variable (p-value= 0.048); work duration (p-value= 0.003); work period (p-value= 0.018), work posture (p-value= 0.001) and MSDs. Health workers need to provide counseling to weavers about the importance of ergonomics to minimize occupational diseases, especially MSDs.